2017
DOI: 10.3389/fpsyg.2017.00378
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Online Behavioral Research Using Crowdsourcing Services in Japan

Abstract: Recent research on human behavior has often collected empirical data from the online labor market, through a process known as crowdsourcing. As well as the United States and the major European countries, there are several crowdsourcing services in Japan. For research purpose, Amazon's Mechanical Turk (MTurk) is the widely used platform among those services. Previous validation studies have shown many commonalities between MTurk workers and participants from traditional samples based on not only personality but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
3
26
0
1
Order By: Relevance
“…We chose an online platform to administer the survey to maximize sample size and minimize cost. However, the lack of control over an online platform has led to commonly observed problems that may affect data quality [ 60 , 61 ]. Most research exploring the suitability of the internet for conducting surveys focusses on the use of online labor markets (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We chose an online platform to administer the survey to maximize sample size and minimize cost. However, the lack of control over an online platform has led to commonly observed problems that may affect data quality [ 60 , 61 ]. Most research exploring the suitability of the internet for conducting surveys focusses on the use of online labor markets (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments reported in this study were both performed online, and therefore guaranteed no control over the experimental conditions. However, it has been shown that online surveys typically yield similar results to those of lab studies [75][76][77], while limiting several disadvantages that are typically associated with central location studies.…”
Section: Limitationsmentioning
confidence: 99%
“…1 Majima et al (2017) found that workers and students were different in terms of demographic status and certain personality traits; however, they demonstrated similar performance on various reasoning tasks. For example, CrowdWorks workers were older, had more extensive work experience, and were less extraverted and agreeable but were more conscientious than students.…”
Section: Crowdwork As a Japanese Participant Pool For Behavioral Stumentioning
confidence: 99%
“…Majima, Nishiyama, Nishihara, and Hata (2017) and the present study adopted the same recruitment method; hence, there would be an overlap of participants between two studies. However, we cannot estimate the degree of overlap because we did not track any identity information to keep anonymity of participants.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation